In vitro mutagenesis in rice (oryza sativa L.) - Ambika Rajendran R (Department of Plant Breeding and Genetics, College of Horticulture, 2005)
An investigation entitled “In vitro mutagenesis in rice (Oryza sativa L.)” was undertaken at the Department of Plant Breeding and Genetics, College of Horticulture, Kerala Agricultural University, Vellanikkara for estimating LD50 values and optimum doses for gamma rays and EMS and identifying desirable plants. Mature, dehulled seeds of variety Ptb-26 were raised in MS medium with different combinations of 2,4-D and Kn. Callus induction studies revealed that MS + 2,4-D 2.0 mgl-1 + Kn 0.5 mgl-1 was the best to induce callus in rice. The same media was used for callus proliferation. Three weeks old subcultured calli was transferred to regeneration MS + NAA 2 mgl-1 + Kn 4 mgl-1 + BAP 0.5 mgl-1 and the shoots obtained were transferred to the rooting medium MS + NAA 2mgl-1 + Kn 0.5 mgl-1. The percentage of success of hardening obtained was 85.20%. Different doses (10Gy, 20Gy, 30Gy, 40Gy, 50Gy and 60Gy) of gamma rays were given to three weeks old subcultured calli and the LD50 value was fixed based on the regeneration percentage. 30Gy was fixed as the LD50 value. Six concentrations of EMS (2mM, 4mM, 6mM, 8mM, 10mM and 12mM) were tried to ascertain the LD50 value based on the regeneration percentage. 4mM was the LD50 value obtained for EMS. Two optimum doses each for the two mutagens below the LD50 value was given to obtain the desirable plants. Ten tissue culture plants for 10Gy, nine for 20Gy, nine for 2mM and eight for 4mM were obtained from this study. They were analysed for biometrical and morphological characters. Based on which the best optimum doses obtained were 20Gy and 4mM for the two mutagens respectively. Significant effect of treatments of gamma rays and concentrations of EMS on genotype was noticed for culm length, plant height, panicles plant-1, panicle length, grains panicle-1and grain yield plant-1. Significant differences were noticed for leaf blade pubescence, leaf blade colour, basal leaf sheath colour and lemma and palea colour. Six tissue culture variants were identified as desirable based on higher panicles plant-1, panicle length, grains panicle-1 and grain yield plant-1.